2022
DOI: 10.1073/pnas.2113891119
|View full text |Cite
|
Sign up to set email alerts
|

When danger strikes: A linguistic tool for tracking America’s collective response to threats

Abstract: In today’s vast digital landscape, people are constantly exposed to threatening language, which attracts attention and activates the human brain’s fear circuitry. However, to date, we have lacked the tools needed to identify threatening language and track its impact on human groups. To fill this gap, we developed a threat dictionary, a computationally derived linguistic tool that indexes threat levels from mass communication channels. We demonstrate this measure’s convergent validity with objective threats in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…This big-data text analysis approach has been recently applied to studying various social issues. It has shown that word use frequency measures were indeed sensitive to social and psychological properties, including social norms, gender norms, response to threat, and romantic relation patterns, as validated with nonlinguistic behavioral data (2,26,36,37).…”
Section: Main Textmentioning
confidence: 78%
“…This big-data text analysis approach has been recently applied to studying various social issues. It has shown that word use frequency measures were indeed sensitive to social and psychological properties, including social norms, gender norms, response to threat, and romantic relation patterns, as validated with nonlinguistic behavioral data (2,26,36,37).…”
Section: Main Textmentioning
confidence: 78%
“…Like all measures in psychology, text-based measures should be examined for their validity (see Table 2). Prior work highlights the importance of benchmarking in historical text analysis (see Choi et al, 2022;Garg et al, 2018;Winkler, 2022). Researchers should validate their data against temporal and geographic ground truth (e.g., survey-based data) to make sure…”
Section: Benchmarkingmentioning
confidence: 99%
“…As an example, consider the recent work of Choi et al (2022), who develop a "threat dictionary". That is, they derive a set of words (or a lexicon) for which they argue their presence in mass communication indicates a cultural feeling of threat.…”
Section: Closed-vocabulary Approachmentioning
confidence: 99%